The political economy of international trade law essays in honor of Robert E. Hudec - Kennedy, Daniel L. M.; Southwick, James D. (Cambridge University Press, 2009)
International experts from law, economics and political science provide in-depth analysis of international trade issues. Attorneys, economists and political scientists adopt a common viewpoint, entitled 'transcending the ostensible'. This approach directs particular attention to the possibility that WTO legal institutions, like other international legal institutions, will function in unexpected ways due to the political and economic conditions of the international environment in which they have been created, and in which they operate. A range of trade problems are considered here. Topics include the constitutional dimensions of international trade law, adding subjects and restructuring existing subjects to international trade law, the legal relations between developed and developing countries, and the operation of the WTO dispute settlement procedure. This will be an essential volume for professionals and academics involved with international trade policy
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Hudec, Robert E.; World Trade Organization; Weltwirtschaft; Foreign trade regulation; International trade; International economic relations; Welthandel; Internationales Handelsrecht; Aufsatzsammlung; Festschrift